Delivering Healthcare Through Teleconsultations: Implications for Offline Healthcare Disparity - Hwang, Elina H.; Guo, Xitong; Tan, Yong; Dang, Yuanyuan (Information Systems Research, 2022)
In this study, we focus on the largely overlooked but important topic: social value created by teleconsultations. Many countries suffer from the geographic imbalance of their medical professionals: there are abundant resources in urban cities but too few in rural areas. Teleconsultations have emerged as a promising solution to reduce this disparity because they can remotely deliver healthcare without relocating medical professionals. Yet it is unclear whether teleconsultations actually mobilize healthcare to underserved areas. To answer this question, we collaborate with a large online healthcare platform and analyze its teleconsulting data together with offline healthcare and regional data. Our results indicate that teleconsultations tend to connect physicians in resourceful regions with patients in underserved areas—a desirable pattern that alleviates the geographic healthcare disparity. However, we also find that social, information, and geography frictions persist. For instance, teleconsultations are less likely to occur as regions become farther apart, and financial and information constraints limit rural patients’ access to teleconsultations. We uncover the underlying mechanisms that drive such frictions and provide recommendations to reduce the frictions that hinder teleconsultations.